2020
DOI: 10.21203/rs.2.21470/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of combined magnesium and zinc supplementation on metabolic status in patients with type 2 diabetes mellitus and coronary heart disease

Abstract: Background: The present research aimed to analyze the impacts of magnesium and zinc supplement on the metabolic level in the patients suffering from CHD (coronary heart disease) and T2DM (type 2 diabetes mellitus). Methods: According to the research design, a randomized, double-blind, placebo-controlled trial has been implemented on 55 women suffering from CHD and T2DM. Therefore, the participants have been randomly divided into 2 groups for taking placebo (n = 28) or 250 mg magnesium oxide plus 220 mg zinc su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The risk of coronary heart disease in diabetic patients is about 2 to 4 times higher than that in normal subjects, and the mortality rate is significantly higher than that in nondiabetic patients [1]. Coronary angiography and autopsy studies have confirmed that CHD in patients with T2DM is more serious or more diffuse than that in nondiabetic patients [2]. Studies have revealed that the proportion of hyperglycemia in people with CHD is about 2/3 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of coronary heart disease in diabetic patients is about 2 to 4 times higher than that in normal subjects, and the mortality rate is significantly higher than that in nondiabetic patients [1]. Coronary angiography and autopsy studies have confirmed that CHD in patients with T2DM is more serious or more diffuse than that in nondiabetic patients [2]. Studies have revealed that the proportion of hyperglycemia in people with CHD is about 2/3 [3].…”
Section: Introductionmentioning
confidence: 99%
“…After receiving traditional therapy along with zinc and magnesium supplements, the overall condition of the patients improved, and the levels of magnesium, zinc, C-reactive proteins, LDL cholesterol, and markers of prooxidant-antioxidant homeostasis normalized. The obtained results indicated the effectiveness of the prescribed therapy [51][52].…”
mentioning
confidence: 67%
“…In Table 1, (1) the purpose of the study is clearly given; (2) the consistency of the included patients; (3) the collection of expected data; (4) the endpoint indicators appropriately reflect the purpose of the research; (5) the objectivity of the evaluation of the endpoint indicators; (6) whether the follow-up time is sufficient; (7) the loss to follow-up rate is less than 5%; (8) whether the sample size is estimated; (9) whether the selection of the control group is appropriate; (10) whether the control group is synchronized; (11) whether the baselines between the groups are comparable; and (12) whether the statistical analysis is appropriate. Scoring method: 0 point means not reported; 1 point means reported but insufficient information; 2 points mean reported and with sufficient information.…”
Section: Characteristics Of Each Studymentioning
confidence: 99%
“…Changes in the trace element concentration in the body are considered to be the main factor leading to the transition of the human body from a healthy to a diseased state [7][8][9][10]. Trace elements, especially zinc ions, are likely involved in the pathogenesis of CHD [11][12][13]. Zinc is an important element in more than 70 enzymes, including superoxide dismutase and glutathione peroxidase.…”
Section: Introductionmentioning
confidence: 99%